Clinical Outcomes Following Tongue Type Calcaneus Fractures. Issue 2 (June 2021) - Burnett, Zachary; Barzee, Brigham M.; Hymes, Robert; Cannada, Lisa K.
Abstract : Background: Calcaneus fractures have serious potential complications. Tongue type calcaneus fractures, in particular, are at risk for secondary soft tissue breakdown due in part to the tension placed on the soft tissue by the forces of the Achilles tendon on the superior fragment of the posterior calcaneal tuberosity. The current literature is limited regarding outcomes in pure tongue type calcaneus fractures. The purpose of this study is to report injury details, treatment, and complications in this group of fractures. Methods: The study is a retrospective study of patients between 2007 and 2015 with tongue type calcaneus fractures. Demographic data and comorbidities were collected for each patient. Clinical data including details of the injury, time to surgery, length of hospital stay, wound complications, additional surgical procedures, and follow-up data were evaluated. Results: There were 25 patients with 26 fractures included in this study, including 7 open fractures. Wound complications occurred in 7 (27%) patients, and fixation failure occurred in 4 (21%) patients. Patients with open fractures reached full healing in less time (2.8±0.4 mo) compared with patients with closed fractures (4±1.3 mo). The difference in time to full healing was not statistically significant ( P >0.05) when comparing smokers and nonsmokers. Conclusions: The literature is limited regarding outcomes of pure tongue type calcaneus fractures. We found these fractures had similar or even higher rates of wound complications compared with other studies investigating intra-articular calcaneus fractures. This is one of the first studies to report on the complication rates associated specifically with these fractures. Level of Evidence: Level IV.